Keefektifan Pendekatan Bertahap dan Penilaian Portofolio dalam Mengembangkan Keterampilan Menulis Siswa Sekolah Dasar - Muhana Gipayana (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
The Effectiveness of Step Approach and Portfolio Assessment in Developing Writing Skills of Elementary School Children. The available effective learning models are expected to help teachers teach more creatively. This quasi-experimental study, conducted in SDN Percobaan and SDN Lowokwaru IV Malang, was intended to find out the effectiveness of step approach and portfilio assessment in developing writing skills of elementary school children. Hypothesis testing of differences between pretest and post-test scores was done to test differences within the groups and between the groups. The results indicated that step approach and portfolio assessment effectively helped develop children’s writing skills.